2008
DOI: 10.1016/j.cpr.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The error-related negativity (ERN) and psychopathology: Toward an endophenotype

Abstract: The ERN is a negative deflection in the event-related potential that peaks approximately 50 ms after the commission of an error. The ERN is thought to reflect early error-processing activity of the anterior cingulate cortex (ACC). First, we review current functional, neurobiological, and developmental data on the ERN. Next, the ERN is discussed in terms of three psychiatric disorders characterized by abnormal response monitoring: anxiety disorders, depression, and substance abuse. These data indicate that incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
441
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(492 citation statements)
references
References 182 publications
40
441
1
5
Order By: Relevance
“…The unexpected finding that anxious subjects show reduced FRNs while at the same time evincing enhanced ERNs is intriguing. That this has been replicated in other trait-anxious subjects by Gu, Huang, and Luo (2009) and reported also by Foti and Hajcak (2009) with depressed subjects not only speaks to the reliability of the FRN as a correlate of these internalizing individual differences, but in conjunction with the ERN may provide important insights into the role of internal and external feedback during performance monitoring and into how these processes may be biased in a number of clinical disorders (see Olvet & Hajcak, 2008, for a brief discussion of externalizing disorders). Lastly, we are encouraged by the possibility that the CRN too may reflect information processing biases.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The unexpected finding that anxious subjects show reduced FRNs while at the same time evincing enhanced ERNs is intriguing. That this has been replicated in other trait-anxious subjects by Gu, Huang, and Luo (2009) and reported also by Foti and Hajcak (2009) with depressed subjects not only speaks to the reliability of the FRN as a correlate of these internalizing individual differences, but in conjunction with the ERN may provide important insights into the role of internal and external feedback during performance monitoring and into how these processes may be biased in a number of clinical disorders (see Olvet & Hajcak, 2008, for a brief discussion of externalizing disorders). Lastly, we are encouraged by the possibility that the CRN too may reflect information processing biases.…”
Section: Resultsmentioning
confidence: 72%
“…As Olvet and Hajcak (2008) point out, the increased sensitivity to errors in depression and anxiety most likely reflects an underlying characteristic common to these internalizing disorders. Identifying the relevant characteristic will be a focus of our future research.…”
Section: The Significance Of Errorsmentioning
confidence: 99%
“…However, we have to acknowledge that because our trait anxiety estimate (based on a standard questionnaire in the literature) likely measures negative affect (or even depression) (e.g., Nitschke et al, 2001;Rossi & Pourtois, in press), enhanced levels of negative affect or internalized personality traits in general, rather than trait anxiety per se (see also Olvet & Hajcak, 2008), may account for the amplitude variations observed at the level of the FRN component in our study.…”
Section: Selective Alteration Of Performance Monitoring In Anxietymentioning
confidence: 99%
“…Because the hypersensitivity to negative events and the tendency to worry about negative outcomes are hallmarks of several affective personality traits or disorders like anxiety and depression (Maner & Schmidt, 2006;Mineka et al, 2003;Wray & Stone, 2005), one may assume that performance monitoring may vary with these affective personality traits. Consistent with this hypothesis, several studies have reported an effect of anxiety or depression on the ERN (e.g., Aarts & Pourtois;2010;Holmes & Pizzagalli, 2008;Olvet & Hajcak, 2008). By contrast, the evidence supporting a systematic modulation of the FRN (and hence the processing of external evaluative feedback) as a function of negative affect is mixed.…”
mentioning
confidence: 96%
“…In the future, studied with ERN has been suggested as an endophenotype in several neuropsychiatric disorders 13,14 .…”
Section: Ern Usefulnessmentioning
confidence: 99%